Valsartan attenuates LPS-induced ALI by modulating NF-κB and MAPK pathways - Zhou, Mi; Meng, Ling; He, Qinke; Ren, Chunguang; Li, Changyi (Frontiers in Pharmacology, 2024)
Background: Acute lung injury (ALI)/acute respiratory distress syndrome (ARDS) is a common respiratory disease characterized by persistent hypoxemia and an uncontrolled inflammatory response. Valsartan, an angiotensin II type 1 receptor antagonist, is clinically used to treat hypertension and has anti-inflammatory and antioxidant effects on gefitinib-induced pneumonia in rats. However, the potential therapeutic effects of valsartan on lipopolysaccharide (LPS)-induced ALI remain unclear. This study investigated the protective role of valsartan in LPS-induced ALI and its underlying mechanisms.Methods: LPS-treated BEAS-2B cells and ALI mouse model were established. BEAS-2B cells were treated with LPS (10 µg/ml) for 24h, with or without valsartan (20, 40, and 80 µM). For ALI mouse models, LPS (5mg/kg) was administered through intratracheal injection to treat the mice for 24h, and valsartan (10 or 30 mg/kg) was injected intraperitoneally twice 2h before and 12h after the LPS injection. Pulmonary functional parameters were examined by an EMKA pulmonary system. Hematoxylin and eosin staining, flow cytometry, CCK-8 assay, qRT-PCR, ELISA, immunofluorescence, western blotting, and related commercial kits were used to assess the pathological damage to the lungs, neutrophil recruitment in the lung tissue and bronchoalveolar lavage fluid (BALF), cell viability, inflammation, oxidative activity, and mucus production, respectively. Potential mechanisms were further explored using network pharmacology and western blotting.Results: Valsartan rescued LPS-reduced cell viability of BEAS-2B cells, improved the pulmonary function, ameliorated pathological lung injury in mice with ALI, ameliorated LPS-induced neutrophil recruitment in BALF and lung tissue of mice, attenuated oxidative stress by increasing the level of SOD and decreasing that of MDA and GSSG, inhibited LPS-induced MUC5AC overproduction, decreased the LPS-induced increase in expression of pro-inflammatory cytokines/chemokines including TNF-α, IL-6, IL-1β, CXCL-1 and CXCL-2, and restored the expression of anti-inflammatory IL-10. Mechanistic studies showed that valsartan inhibits LPS-induced phosphorylation of nuclear factor-kappa B (NF-κΒ) and mitogen-activated protein kinases (MAPKs) including P38, extracellular signal-regulated kinase (ERK), and c-Jun N-terminal kinase (JNK) in both LPS-treated cells and the mouse model of ALI.Valsartan protects against LPS-induced ALI by attenuating oxidative stress, reducing MUC5AC production, and attenuating the inflammatory response that may involve MAPK and NF-κΒ pathways.